Ambulatory Intravenous Antibiotic Therapy in Quebec: The Hôpital Charles LeMoyne Experience in 1996 - Laurent Delorme; Charles Frenette; Isabelle Le Corre; Julie Duchesne; Carole Delorme; Pauline Plourde (Canadian Journal of Infectious Diseases)
From January 1, 1996 to December 31, 1996, 343 patients received outpatient intravenous antibiotic therapy at Charles LeMoyne Hospital, a 436-bed, acute care hospital in Greenfield Park, south of Montréal, Québec. The infectious diseases department saved 2660 bed-days using outpatient therapy. The mean duration of outpatient therapy was 7.76 days; 81.6% of patients were admitted to the program directly from the emergency room, or outpatient hospital clinics or private offices in the community. Hospitalized patients constituted only 18.4% of admissions to the outpatient intravenous antibiotic therapy program. Forty per cent of the surgical/medical staff participated in the program and they were able to generate a significant impact by diverting patients to outpatient therapy. Two types of patients can benefit from an outpatient intravenous antibiotic therapy program. One group of patients needs empirical short term therapy and can be switched to oral sequential therapy after two to five days of outpatient intravenous antibiotic therapy. A second group of patients needs specific long term therapy for the full duration of the antibiotic therapy. Empirical short term therapy can be managed by emergency department or hospital-based primary physicians, or medical/surgical specialists. Specific long term therapy can be managed by microbiology/infectious disease specialists or medical/surgical specialists. Hospitals that want to relieve pressure on emergency rooms and hospital bed demands should create facilities for both types of patients. Cefazolin and gentamicine/tobramycine were the most commonly used antibiotics in empirical short term therapy and in terms of number of patients treated. Ceftriaxone and vancomycin were most commonly used for long term therapy. The Drug acquisition antibiotic cost was $73,117 but constituted only 20% of the total outpatient intravenous antibiotic therapy cost. The per diem ambulatory cost was $140/patient/day.